Plasma‐Made (Ni0.5Cu0.5)Fe2O4 Nanoparticles for Alcohol Amination under Microwave Heating. Issue 16 (2nd August 2019) - Li, Alain You; Dumaresq, Nicolas; Segalla, Andréanne; Braidy, Nadi; Moores, Audrey
Abstract: Amine N ‐alkylation is a process involved in the production of a wide range of chemicals. Here we describe the synthesis of well‐defined (Ni0.5 Cu0.5 )Fe2 O4 magnetic nanoparticles by plasma induction, and their successful application to amine N ‐alkylation using alcohols as coupling agents through a borrowing hydrogen pathway. Plasma induction allows precise morphology and size control over nanoparticle synthesis, while allowing the one‐pot production of decagram quantities of material. Up to date, such nanoparticles have never been applied for organic reactions. By coupling high‐end characterization techniques with catalytic optimization, we showed that small Cu(0) satellite nanoparticles played an essential role in alcohol oxidation, whereas both Ni and Cu were required for the last step of the reaction. Using elemental mapping, we demonstrated that catalyst deactivation occurred through a leaching/re‐deposition mechanism of Cu and Ni. The reactions were conducted under microwave conditions, which exerted a positive effect on catalytic activity. Finally, the catalyst was active at low metal loadings (2 mol%) even on the gram‐scale, and affording unprecedented TON for this reaction catalyzed by Ni/Cu bimetallic systems (19). Abstract : The three‐body solution . A noble metal‐free, magnetically recyclable (Ni0.5 Cu0.5 )Fe2 O4 catalyst was made under plasma conditions. It catalyzes alcohol amination through a hydrogen borrowing pathway. The role of each metal in the reaction, as well the mechanism for catalytic deactivation was identified, aided by EELS spectroscopy.